2005
DOI: 10.1111/j.1538-7836.2005.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antiplatelet effect of clopidogrel in patients whose platelets are least inhibited by aspirin: a randomized crossover trial

Abstract: Summary. Objective: We aimed to determine whether adding clopidogrel to aspirin in patients at high risk of future cardiovascular events would suppress laboratory measures of the antiplatelet effects of aspirin; and have greater platelet inhibitory effects in patients with the least inhibition of platelets by aspirin. Methods: We performed a randomized, double-blind, placebo-controlled, crossover trial, comparing clopidogrel 75 mg day )1 versus placebo, in 36 aspirin-treated patients with symptomatic objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
(33 reference statements)
4
35
1
Order By: Relevance
“…These findings parallel those reported in the literature. 16,17 As expected, neither SCH 602539 nor cangrelor (nor the combination of the 2) had any notable effect on coagulation parameters, a finding that is consistent with the fact that these agents interact with specific platelet receptors and do not interfere with the coagulation cascade. SCH 602539 is structurally related to vorapaxar, a PAR-1 antagonist being evaluated in 2 large ongoing clinical trials (secondary prevention and acute coronary syndromes; clinicaltrials.gov identifiers: NCT00526474 and NCT00527943).…”
Section: Discussionsupporting
confidence: 80%
“…These findings parallel those reported in the literature. 16,17 As expected, neither SCH 602539 nor cangrelor (nor the combination of the 2) had any notable effect on coagulation parameters, a finding that is consistent with the fact that these agents interact with specific platelet receptors and do not interfere with the coagulation cascade. SCH 602539 is structurally related to vorapaxar, a PAR-1 antagonist being evaluated in 2 large ongoing clinical trials (secondary prevention and acute coronary syndromes; clinicaltrials.gov identifiers: NCT00526474 and NCT00527943).…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, aspirin resistance has been defined by incomplete suppression of urinary 11-dhTxB 2 excretion for which platelet response to ADP may be important [6, 8, 9]. In our study measurement of urinary 11-dhTxB 2 excretion, a marker for inhibition of thromboxane A 2 production, does not distinguish between those with complete or incomplete inhibition of platelet aggregation [1, 2].…”
Section: Discussionmentioning
confidence: 78%
“…Although using a different marker for platelet inhibition, Grotemeyer et al [3 ]suggested that measured antiplatelet response to aspirin predicts clinical efficacy and others have found this for clopidogrel as well [4]. For those with incomplete inhibition of platelet response to aspirin, a higher dose of aspirin or the addition of clopidogrel may in certain patients achieve complete inhibition of platelet aggregation [1, 2, 5, 6]. In addition to the markers of platelet inhibition used by Helgason et al and Grotemeyer et al, Santos et al [7] described patients taking aspirin at doses associated with suboptimal inhibition of platelet recruitment due to inadequate inhibition of erythrocyte prothrombotic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Eikelboom et al [89] raised the possibility that the clinical benefits of adding clopidogrel to aspirin may be greatest in patients whose platelets are least inhibited by aspirin. In another study, the addition of clopidogrel to aspirin provided greater inhibition of platelets and could overcome aspirin resistance [90] .…”
Section: Possible Treatment Of Aspirin Resistancementioning
confidence: 99%